PENGARUH BRAND IMAGE, IKLAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK EMINA (Pada Mahasiswa Ilmu Komunikasi Universitas Slamet Riyadi Surakarta) - Agnestasya, Adhelina; Riyanto, Buddy; Itasari, Andri Astuti (Solidaritas, 2024)
The aim of this research is to determine the influence of brand image, advertising and product quality on purchasing decisions for Emina products. This research was conducted in the Communication Science environment, Faculty of Social Sciences, Slamet Riyadi University, Surakarta, which has used or used Emina products. This research uses a quantitative approach with an explanatory method. The sampling technique in this research uses simple random sampling and the total sample of Communication Science students used in this research is 100 students. The results of the research in this thesis show that the t-value of brand image has a positive and significant effect of 2.49 with a p-value of 0.014 <0.05 on purchasing decisions. Advertising has a positive and significant effect of 2.255 with a p-value of 0.026 <0.05 on purchasing decisions. Product quality has a positive and significant effect of 4.803 with a p-value of 0.000 <0.05 on purchasing decisions. Meanwhile, the results of the f-calculated value of brand image, advertising, product quality have a positive and significant effect of 67,857 with a p-value of 0.000 <0.05 on purchasing decisions. Keywords: Brand Image, Advertising, Product Quality, Emina and Purchasing Decisions